Convenient formal synthesis of (+/-)-paroxetine - Chavan, Subhash P.; Khobragade, Dushant A.; Pathak, Ashok B.; Kalkote, Uttam R. (Synthetic Communications, 2007)
A formal total synthesis of antidepressant (+/-)-paroxetine employing a solvent-free Heck reaction is disclosed.
Keywords: antidepressants; carbamate; electrophile; Heck reaction; piperidines